2014
DOI: 10.1111/ggi.12340
|View full text |Cite
|
Sign up to set email alerts
|

Status of prevalence study on multimorbidity of chronic disease in China: Systematic review

Abstract: It is imperative to provide a more uniform method to improve the validity of prevalence studies on multimorbidity. However, the status of prevalence studies on multimorbidity of chronic disease is still yet to be confirmed in China. The objective of the present systematic review was to evaluate the variance across prevalence studies and to explore possible explanations for variations in China. Published literature was obtained from four databases. The studies that described the prevalence of multimorbidity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 24 publications
7
56
3
Order By: Relevance
“…It fits well with the range of the overall prevalence of multimorbidity from a systematic review of 9 published studies in China (6.4%–76.5%) [27]. A study with a large sample conducted in Southern China showed that the prevalence of multimorbidity among the elderly people was 47.5% [18], consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…It fits well with the range of the overall prevalence of multimorbidity from a systematic review of 9 published studies in China (6.4%–76.5%) [27]. A study with a large sample conducted in Southern China showed that the prevalence of multimorbidity among the elderly people was 47.5% [18], consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…10,16 These inconsistencies might arise from at least the following factors: residents in poorer countries lack access to health services and diagnoses, and therefore the prevalence of multimorbidity is underreported; 3,17 richer and poorer countries are at different stages of the health transition, and the conclusions obtained from richer countries do not apply to poorer countries; 18 or from differences in study design. 12,19,20 Further evidence could clarify the situation.…”
Section: Introductionmentioning
confidence: 98%
“…Pati et al found the prevalence of multimorbidity in South Asia varied widely, mostly lower than those reported in high‐income countries, but most studies were based on small samples . We searched both Chinese and English language databases for studies of multimorbidity prevalence in China and found extremely divergent reports; for example, the proportion of older people reported with more than one chronic disease ranged from 6.4% to 90.5% …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have measured MCC as the presence of comorbid conditions in the context of a single disease. These studies have used pre-existing [13], co-existing [14], and newly developed conditions in the context of an index chronic condition [15]. Within the framework of an index disease, these combinations have been grouped using a conceptual framework based on clinical management of the index disease.…”
Section: Introductionmentioning
confidence: 99%